Esterification of enzymatically treated macaw palm oil catalyzed by heteropolyacid supported onto Nb2O5 - Machado, Sara A. (2022)
An approach to producing biodiesel is the esterification of free fatty acids with an acyl acceptor. Free fatty acids can be produced through the hydrolysis of acylglycerols and represent a somewhat challenging feedstock for the production of biodiesel due to slower kinetics and the production of water in the reaction. The purpose of this work was to demonstrate the feasibility of a Keggin-structured heteropolyacid, H3PW12O40 (HPW) supported onto Nb2O5 to be used as a catalyst for the reaction of free fatty acids with ethanol to produce ethyl esters that comply with biodiesel norm values. The use of heteropolyacids as heterogeneous catalysts may present advantageous operational benefits, including the tolerance to residual water present in the medium and the potential for reusability. The catalyst was prepared via impregnation of HPW onto Nb2O5 and was characterized in terms of acidity and surface properties. The enzymatic hydrolysis of macaw palm oil yielded a feedstock containing a free fatty acid content greater than 93%. The hydrolysate was assessed as a reactant for the esterification reaction, evaluating temperature, molar ratio, and catalyst amount, leading to optimal conversions greater than 99% with viscosity and density within the regulatory limits for biodiesel. The use of heterogeneous acid catalysts, such as HPW/Nb2O5, represents a potentially feasible alternative to unlocking the potential of working with challenging feedstocks as oil hydrolysates.